Severe fever with thrombocytopenia syndrome (SFTS) in Thailand: using a one health approach to respond to novel zoonosis and its implications in clinical practice - Chalo Sansilapin; Ratanaporn Tangwangvivat; Curtis S. Hoffmann; Chanatip Chailek; Paisin Lekcharoen; Nattakarn Thippamom; Sininat Petcharat; Piyanan Taweethavonsawat; Supaporn Wacharapluesadee; Rome Buathong; Takeshi Kurosu; Tomoki Yoshikawa; et al. (BMC, 2024)
Abstract Severe fever with thrombocytopenia syndrome (SFTS), a tick-borne disease caused by Dabie bandavirus (SFTSV) is an emerging infectious disease of substantial concern in East Asia. In 2019, Ongkittikul S et al. reported the first case of SFTS in Thailand. Our report describes a One Health investigation of SFTS zoonosis examining the index case and suspected animal reservoirs using real-time RT-PCR and immunoassays. We add to the report on the first confirmed case of SFTSV infection in a human in Thailand by conducting a limited but informative One Health surveillance study. Dogs and cats tested positive for SFTSV antibody using IgG ELISA. We conclude that domestic dogs and cats might serve as potential reservoirs for SFTSV spread due to their closer proximity to the index case than other non-domestic animals. Notably, we did not detect SFTSV in synanthropic cats or dogs-nor did we detect SFTSV in Rhipicephalus sanguineus ticks-using RT-PCR. We propose that One Health investigations coupling genomic and serologic assays in response to new SFTS cases could play a pivotal role in preventing and managing SFTS among humans and animals in East Asia. As such, we are establishing a collaborative response to SFTS in Thailand through human outbreak investigations that align with principles of One Health, through environmental surveys and animal RT-PCR and immunoassays. Our investigation highlights the importance of coupling RT-PCR with seroprevalence assays as principal elements of One Health surveillance for SFTS in order to shed light on potential animal reservoirs and track emerging zoonosis.